2014
DOI: 10.1007/s00464-014-3817-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of minimizing access trauma in laparoscopic colectomy in patients with IBD

Abstract: Laparoscopic procedures for colectomy and proctocolectomy are safe and effective techniques for patients with colon involvement and IBD. Minimizing the access trauma in laparoscopic colectomy offers a potential advantage of reduced surgical site infections, especially for frequently immunosuppressed IBD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…The place of STC with ileostomy formation for acute severe colitis, which does not respond to medical therapy, is well established . In the last decade a trend towards minimally invasive surgery has been observed and this enthusiasm extends into the field of inflammatory bowel disease . We present herein a large cohort study from a single tertiary centre, analysing the approaches and outcomes of STC for UC over 8 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The place of STC with ileostomy formation for acute severe colitis, which does not respond to medical therapy, is well established . In the last decade a trend towards minimally invasive surgery has been observed and this enthusiasm extends into the field of inflammatory bowel disease . We present herein a large cohort study from a single tertiary centre, analysing the approaches and outcomes of STC for UC over 8 years.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive surgery is well established in colorectal surgery, including surgery for inflammatory bowel disease . The feasibility and safety of laparoscopic STC for UC have been recognized in several studies .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the risk of postoperative infection can be reduced in patients with IBD who frequently use immunosuppressants. For patients who require a prophylactic ostomy, the diseased bowel may be delivered through an incision at the ostomy without the need for an additional auxiliary incision[ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the RECIPE trial (Reduction of Postoperative Wound Infections by Antiseptica), which was conducted at the department for general, visceral, and vascular surgery of the Charité-Campus Benjamin Franklin, we showed a reduction in SSI in elective laparotomies by intraoperative subcutaneous wound irrigation with polyhexanide solution compared to wound irrigation with saline [16]. In IBD patients, laparoscopic procedures offer a potential advantage, especially for frequently immunosuppressed patients, to reduce SSIs [17]. Other studies have shown the influence of avoiding razors for hair removal, decolonization, maintaining normothermia, and perioperative glycemic control [18].…”
Section: Introductionmentioning
confidence: 94%